Phytochemical and in vitro pharmacological evaluation of Phlomis Pungens - Okur, Mehmet Evren; Karadağ, Ayşe Esra; Reis, Rengin; Sipahi, Hande; Arslan, Rana; Demirci, Betül; Demirci, Fatih (Ankara University, 2022)
Objective: This study aimed to investigate the in vitro wound healing, anti-inflammatory, antimicrobial and antioxidant activity of Phlomis pungens Willd. extract derived from the aerial parts. Material and Method: The phytochemical analysis was performed using GC-MS in order to identify the volatile components of the bioactive Hex extract. The wound healing activity of P. pungens extract was evaluated based on in vitro antimicrobial, antioxidant, anti-inflammatory, and, scratch activity was studied. In addition, the in vitro cytotoxicity of the extract was also evaluated. Result and Discussion: P. pungens methanol extract depicted a 5-LOX inhibitory activity at 78.2µg/mL (IC50), while the antioxidant activity by DPPH radical provided an IC50=2.41mg/mL, and the ABTS radical showed IC50=3.32mg/mL, respectively. The extract showed dose-dependently anti-inflammatory activity while L-NAME and P. pungens methanol extract significantly decreased LPS stimulated PGE2 production. According to the scratch assay results, all treatments led to an increase in cell migration rate with a dose-dependent effect. Our findings suggested that P. pungens methanol extract may have a role in wound healing according to the scratch test, and it is thought that its antioxidant and anti-inflammatory activity also contributed. Further evaluations are ongoing to confirm the in vitro activity under in vivo conditions.

Amaç: Bu çalışmada, Phlomis pungens Willd. topraküstü kısımlarından elde edilen ekstrelerin in vitro yara iyileşmesi, antiinflamatuar, antimikrobiyal ve antioksidan aktivitesinin araştırılması amaçlanmıştır. Gereç ve Yöntem: Biyoaktif hekzan ekstresinin uçucu bileşenlerini belirlemek için fitokimyasal analiz GC-MS kullanılarak yapılmıştır. P. pungens ekstresinin yara iyileştirme aktivitesi, in vitro antimikrobiyal, antioksidan, antiinflamatuar etkinlikleri değerlendirilmiş ve ek olarak ekstrenin in vitro sitotoksisitesi de değerlendirilmiştir. Sonuç ve Tartışma: P. pungens metanol ekstresi, 78,2 µg/mL'de (IC50) 5-LOX inhibe edici aktivite gösterirken, DPPH yöntemi ile antioksidan aktivitesi IC50=2.41mg/mL ve ABTS IC50=3.32 mg/mL olarak bulunmuştur. Ekstre, doza bağlı olarak anti-inflamatuar aktivite gösterirken, L-NAME ve P. pungens metanol ekstresi, LPS ile uyarılan PGE2 üretimini önemli ölçüde azaltmıştır. Strach metodu sonuçlarına göre doza bağlı etki ile hücre göç hızında bir artış gözlemlenmiştir. Bulgularımız, starch testine göre P. pungens metanol ekstresinin yara iyileşmesinde rol oynayabileceğini ve antioksidan ve antiinflamatuar aktivitesinin de katkıda bulunduğu düşündürmüştür. İn vivo koşullar altında in vitro aktiviteyi doğrulamak için başka değerlendirmeler devam etmektedir.
Phlomis Pungens’in fitokimya ve in vitro farmakolojik etkilerinin değerlendirilmesi
Keywords: Cell Culture; Fibroblast; Inflammation; Lamiaceae; Macrophage; Hücre Kültürü; Fibroblast; Enflamasyon; Lamiaceae; Makrofaj